Enhancing Elementary School English Learning: The Power of AI-Based Problem-Based Learning (PBL) Model - Elida, Yusti; Oktadela, Resy; Hadiyanti, Putri Octa (Journal of English Language and Education, 2025)
The integration of Artificial Intelligence (AI) in language learning has the potential to enhance student engagement and improve educational outcomes. However, research on its effectiveness in elementary English education remains limited. This study examines the impact of AI-assisted Problem-Based Learning (PBL) on students’ English proficiency, engagement, and motivation at SD IT Imam Syafii Cendikia Pekanbaru. A quasi-experimental design was employed, with an experimental group receiving AI-powered PBL instruction and a control group following traditional methods. Pre-test and post-test assessments, engagement observations, and motivation surveys were used for data collection. The findings reveal that the experimental group showed a 31.1% improvement in English proficiency, significantly higher than the control group’s 15.9%. Additionally, AI-assisted PBL fostered greater student engagement and motivation. These results suggest that AI-enhanced PBL is an effective instructional approach for improving elementary students’ English learning outcomes.